Traditional Bioethical Mechanisms for the Humanization of Scientific Knowledge and their Transformation in the Era of Open Science - Sokolchik, Valerya (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
The article examines traditional bioethical mechanisms implemented to oversee scientific knowledge for its humanization. These fundamental mechanisms include the incorporation of bioethical principles and guidelines into recommendations for researchers, voluntary informed consent, and ethical review conducted by (bio)ethics committees. The methodological foundation of traditional bioethical oversight of scientific knowledge is based on bioethics' emphasis on transdisciplinarity, practical orientation, pluralistic universalism, personal focus, and collegial decision-making. In the context of the emergence of open science, the aforementioned mechanisms inevitably undergo changes. The new scientific paradigm that formed in the 21st century is characterized primarily by the pervasive use of artificial intelligence tools, as well as the development of transparency and openness of knowledge to society, which further emphasizes issues of protecting humans and nature, and the humanistic orientation of research. Alongside the formation of new bioethical means of knowledge oversight in open science, traditional mechanisms continue to be used. They are significantly modernized in the contemporary world, their scope of application expands beyond biomedicine (as was established in classical bioethics), and national specifics of their legitimization and application gain greater importance. Based on the study of international experience and the experience of the Republic of Belarus, the research proposes modern pathways for transforming the activities of (bio)ethics committees, practices of voluntary informed consent, and the development and improvement of international and national advisory documents on bioethical issues.
Keywords: bioethical mechanisms; scientific research; open science; humanization; informed consent; (bio)ethical committees; advisory documents